2018
DOI: 10.1007/s12672-018-0339-4
|View full text |Cite
|
Sign up to set email alerts
|

Increased High Molecular Weight FGF2 in Endocrine-Resistant Breast Cancer

Abstract: Endocrine resistance may develop as a consequence of enhanced growth factor signaling. Fibroblast growth factor 2 (FGF2) consists of a low and several high molecular weight forms (HMW-FGF2). We previously demonstrated that antiprogestin-resistant mammary carcinomas display lower levels of progesterone receptor A isoforms (PRA) than B isoforms (PRB). Our aim was to evaluate the role of FGF2 isoforms in breast cancer progression. We evaluated FGF2 expression, cell proliferation, and pathway activation in models … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…FGF2 is well characterized and possesses the typical features of the FGF family, which plays significant roles in various physiological and pathological processes 33. Previous studies reported that FGF2 is strongly expressed in various tumors, such as gastric cancer,34 breast cancer,35 glioma,36 and lung cancer 37. FGF2 is also highly expressed in EOC20 and has oncogenic activity in EOC formation and progression 2123.…”
Section: Discussionmentioning
confidence: 99%
“…FGF2 is well characterized and possesses the typical features of the FGF family, which plays significant roles in various physiological and pathological processes 33. Previous studies reported that FGF2 is strongly expressed in various tumors, such as gastric cancer,34 breast cancer,35 glioma,36 and lung cancer 37. FGF2 is also highly expressed in EOC20 and has oncogenic activity in EOC formation and progression 2123.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we propose that autocrine or paracrine FGF2, probably produced by stromal CAFs, activates FGFRs and downstream signaling pathways, which in turn activate ERα and classic and novel PR isoforms. These activated receptors form complexes that play key roles inducing the transcription of MYC , a master cancer gene.…”
Section: Discussionmentioning
confidence: 98%
“…Myc inhibitor, antiestrogen, or antiprogesterone can reverse the effect of FGF2 induction [ 37 ]. Ana et al studied the role of FGF2 subtype in the progression of BC by evaluating the expression and location of FGF2 in 81 cases of BC [ 38 ]. They found that FGF2 was expressed in 55.6% of breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%